(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This essay aims to reflect on the need to rethink curricula, methodological approaches, teaching plans, and training spaces in the body arts in light of the socio-environmental challenges present in the era we live in, the Anthropocene, bringing ecosomatics into the debate: a set of ecological practices that aims to create engaged and responsive thoughts/actions.